Hemispheric asymmetries in human beings and monkeys - Jason, G (1981)
Part I. Patients with unilateral brain damage were given a number of tests to investigate the nature of left hemisphere specialization for complex sequential movements of the hand and arm. It was concluded that the left hemisphere deficit was one of memory rather than performance. There was no specific left hemisphere deficit in the ordering of multiple motor acts. Traditional apraxia tests produced results consistent with the interpretation of normal left hemisphere specialization for memory (but not ordering or execution) of motor acts. There was no left hemisphere deficit in producing a large number of different positions when there were no constraints on the exact positions produced. Firm conclusions could not be drawn to questions regarding the importance or relevance to the asymmetry of the motor nature of the tasks, the inclusion of more than one element or motion in motor memory tasks, or the involvement of proximal v. distal muscles in motor memory tasks. Little information was found on the relationship between motor and language functions of the left hemisphere. It was hypothesized that there are two broad stages of motor function: generation of motor "target" acts (which is lateralized to the left hemisphere) and the ordering and execution of these acts (which is not lateralized). Part II. The hypothesis that functional neural asymmetries exist in rhesus monkeys was tested using a task which in human beings is lateralized to the right hemisphere: the task required discrimination between two squares, one containing a dot located exactly in the centre, and the other containing a dot displaced vertically from centre. Pre- and post-operative threshold measures were taken. Animals with a left occipital lobectomy combined with a splenial section were worse post- operatively than pre-operatively; animals with similar right-sided lesions were better. Hand preference was probably unrelated to this asymmetry, and to hand competence on a visually-guided reaching task.